Energy Efficiency Optimization for D2D Underlay Communication in Distributed Antenna System over Composite Fading Channels - Wang, G. Y.; Dhaka, A.; Teng, T.; Yu, K. (Společnost pro radioelektronické inženýrství, 2022)
Device-to-Device (D2D) communication is a potential technology to improve the spectral and energy efficiency (EE) of communication networks. In this paper, we study energy-efficient power allocation (PA) schemes in uplink distributed antenna system (DAS) with device-to-device underlay communication. Our goal is to maximize the total EE of all D2D pairs while guaranteeing the data rate and transmit power requirements of the cellular user and D2D links. To solve this non-convex constrained optimization problem, we propose an energy-efficient near-optimal PA algorithm based on the concave-convex procedure and fractional programming theory. This near-optimal algorithm can achieve the EE performance close to the optimal exhaustive search. To reduce the complexity, we furthermore present an efficient sub-optimal algorithm with the antenna selection method which can obtain the closed-form power allocation expressions. Simulation results demonstrate the significant EE performance of our proposed PA schemes.
Keywords: Device-to-Device (D2D) communication; energy efficiency; power allocation; distributed antenna system; rate constraint